Isolation and screening of lactic acid bacteria, Lactococcus lactis from Clarias gariepinus (African catfish) with potential use as probiotic in aquaculture - Tengku Abdul Hamid, Tengku Haziyamin; Khan Chowdhury, Ahmed Jalal; Jalil, Muhammad Fauzi; Azhar, Nur Shazana (Academic Journals, 2012)
In aquaculture probiotic feeding could play a crucial role in developing microbial control strategies, since disease outbreaks are recognized as important constraints to aquaculture production and the fear of antibiotic resistance. In this study, lactic acid bacteria (LAB) strains from the intestinal tissue of African catfish Clarias griepinus were successfully screened, characterized and identified. The isolates (S1#8, S1#9, S1#10, S1#18, S1#19 S1#20 and S1#21) shared common morphological characteristics of LAB such as non-sporulating, Gram positive cocci or cocco-bacilli shape. These were the dominating morphology found in the catfish, as compared to other types of LABs reported to be found in freshwater fishes. All of the 35 isolates have the ability to utilize lactose as part of their metabolism process and showed negative reactions towards catalase test. These isolates were also tested for antimicrobial activities using disc diffusion assay against indicator Salmonella typhimurium and Escherichia coli. Based on the partial 16S rRNA sequences, the selected LAB isolates belonged to a member of Lactococcus lactis with 98% DNA similarity. This strain can be used as probiotic in aquaculture feeding.